Agricultural land use and pond management influence spatial-temporal variation of CH4 and N2O emission fluxes in ponds in a subtropical agricultural headstream watershed - Fan, Manman; Zhang, Wenzhao; Wu, Jingtao; Zhou, Jiaogen (Frontiers in Environmental Science, 2022)
Small water bodies are hotspots of biogeochemical cycles with large spatial and temporal heterogeneity of their greenhouse gas emission fluxes. To reveal the spatial and temporal variabilities of methane (CH4) and nitrogen dioxide (N2O) emission fluxes in small water bodies in subtropical agricultural headwater watersheds, monthly measurements of CH4 and N2O fluxes were performed in 53 ponds from May 2018 to July 2020. Results showed that the fluxes of CH4 and N2O exhibited distinct spatial and temporal variations, and generally showed a trend of high emission rate in summer and low emission rate in winter. Agricultural land use and pond management had important impacts on CH4 and N2O emission fluxes in ponds. The CH4 and N2O emission fluxes were significantly higher in the ponds with the landscape of farmland, tea plantation and residential area than those of forest, which might be relevant to the eutrophication of pond water bodies. The mean N2O emission flux in intensive fishing ponds was much higher than that in grass-fed fishing ponds and no fishing ponds. Moreover, the sustained-flux global warming potential (SGWP) in the eutrophic pond water bodies of farmland, tea plantation and residential area are significantly higher than that in oligotrophic water bodies of forest ponds. Our CH4 and N2O emission results suggest that the reduction potential of 4.98 kg C ha-1 y-1 for CH4 and 0.42 kg N ha-1 y-1 for N2O will occur in future if ecological management measures are implemented to improve the pond water quality from eutrophication to oligotrophic conditions.